2014
DOI: 10.1002/hfm.20563
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Presence for Customer Experience in a Virtual Environment: Using a Nuclear Power Plant as an Example

Abstract: In contrast to experiences offered by traditional media, this study used a three‐dimensional virtual environment to evaluate customer experiences. The aims of this study were twofold: first, to investigate whether virtual interaction can impress customers in a visual or auditory sense and thereby further induce “presence”; and second, to understand how to provide a better sense of presence by using virtual interactions. This study used a nuclear power plant control room to construct virtual customer experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…One way to measure presence is to observe how people physically react to stimulation; we can call this behavioral presence (Witmer and Singer, 1998;Zeltzer, 1992;Meehan et al, 2002;Ijsselsteijn et al, 2002;North, 2002;Riva et al, 2007;Lee, Chou & Sun, 2015). Behavioral presence focused mainly on the movements of the subjects and on spontaneous speech.…”
Section: Measuring Presencementioning
confidence: 99%
See 2 more Smart Citations
“…One way to measure presence is to observe how people physically react to stimulation; we can call this behavioral presence (Witmer and Singer, 1998;Zeltzer, 1992;Meehan et al, 2002;Ijsselsteijn et al, 2002;North, 2002;Riva et al, 2007;Lee, Chou & Sun, 2015). Behavioral presence focused mainly on the movements of the subjects and on spontaneous speech.…”
Section: Measuring Presencementioning
confidence: 99%
“…To properly measure presence, several questionnaires have been suggested Lombard & Ditton, 1997;Sheridan, 1996;Slater et al, 1994;Slater, 1999;June et al, 2009;North et al, 2002;Lin et al, 2002;Lee et al, 2015). Based on the research briefly described above, particularly the questionnaire originally developed by Slater et al (1994), questionnaires that measured subjective self-reports were administered immediately after the completion of the simulation sessions for both IVE and TVRE experiments.…”
Section: Measuring Presencementioning
confidence: 99%
See 1 more Smart Citation
“…() found that the doctors who have been trained using the VR system apparently had better‐quality surgery skills. VR technology has also been widely utilized in trainings for design, manufacturing, transportation, military, and nuclear power plant (Chaffin, ; Chung, Shewchuk, & Williges, ; Duarte et al., ; Fuhua, Duffy, & Su, ; Hue, Delannay, & Berland, ; Lee, Chou, & Sun, ; Nathanael, Mosialos, Vosniakos, & Tsagkas, ; Vilar, Rebelo, F., & Noriega, 2016; Wu, Mu, Yang, & Gu, ). Instead of the effects of VR on mental workload (MWL), applications of VR have often focused on training performance.…”
Section: Introductionmentioning
confidence: 99%